Innovation of Gel Based on Kopasanda Leaf Extract (Chromolaena odorata) in Supporting Burn Wound Healing in Rabbits - Ervianingsih Ervianingsih; Abd Razak; Nur Waqia Akbar; Waode Suiyarti; Sunarto Sunarto S (Postgraduate, University of Mataram, 2025)
Inflammation is the body's physiological response to harmful stimuli, such as infection and trauma, which can lead to tissue damage. The long-term use of synthetic anti-inflammatory drugs has adverse side effects, so safer alternatives to natural ingredients are needed. This study aims to test the anti-inflammatory activity of ethanol extract gel preparations of star fruit leaf (Averrhoa bilimbi L) in mice (Mus musculus). The method used is the method of carrageenan induction on the soles of the feet of mice to observe the effects of inflammation. Gel preparations were administered in various concentrations (5%, 10%, and 15%) and compared with negative controls (gel base) and positive controls (sodium diclofenac). The results showed that the preparation of star fruit leaf extract gel was able to significantly inhibit swelling at concentrations of 10% and 15%. This activity is thought to come from the content of flavonoids and tannins in star fruit leaves which are known to have anti-inflammatory effects. This research provides a scientific basis that star fruit leaf gel preparations have potential as an alternative to natural anti-inflammatory drugs.